2008
DOI: 10.1091/mbc.e08-09-0896
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiolipin Transacylase, Tafazzin, Associates with Two Distinct Respiratory Components Providing Insight into Barth Syndrome

Abstract: Mutations in the mitochondrial cardiolipin (CL) transacylase, tafazzin (Taz1p), result in the X-linked cardioskeletal myopathy, Barth syndrome (BTHS). The mitochondria of BTHS patients exhibit variable respiratory defects and abnormal cristae ultrastructure. The biochemical basis for these observations is unknown. In the absence of its target phospholipid, CL, a very large Taz1p complex is missing, whereas several discrete smaller complexes are still observed. None of the identified Taz1p complexes represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 53 publications
8
89
1
Order By: Relevance
“…Importantly, studies that previously reported abnormal mitochondrial morphology in ⌬crd1 and ⌬taz1 yeast never reported the penetrance of the observed defects (19,52). Furthermore, our results indicate that the genetic background contributes to mitochondrial morphology.…”
Section: Remodeling Is Not Required To Maintain Mitochondrialsupporting
confidence: 44%
See 2 more Smart Citations
“…Importantly, studies that previously reported abnormal mitochondrial morphology in ⌬crd1 and ⌬taz1 yeast never reported the penetrance of the observed defects (19,52). Furthermore, our results indicate that the genetic background contributes to mitochondrial morphology.…”
Section: Remodeling Is Not Required To Maintain Mitochondrialsupporting
confidence: 44%
“…Miscellaneous-Isolation of mitochondria, preparation of yeast cell extracts, blue native-PAGE, mitochondrial respiration, phospholipid analysis, and immunoblotting were performed as described previously (12,18,52). Statistical comparisons were performed by one-way analysis of variance compared with wild type using SigmaPlot 11 software (Systat software, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CL is the signature lipid of mitochondria, where it is an important constituent of the inner membrane, essential for supercomplex formation, oxidative phosphorylation (i.e., mitochondrial energy metabolism), and protein import, and is capable of triggering mitophagy and mitochondria-mediated apoptosis (8)(9)(10)(11)(12)(13)(14)(15)(16). Because the remodeling of CL is deficient in BTHS, biochemical abnormalities in patients include a decreased level of mature CL (CLm), an increased level of monolysocardiolipin (MLCL), and altered CL acyl composition [i.e., the presence of immature CL (CLi) species].…”
mentioning
confidence: 99%
“…Thus, potentially, many processes that result in impaired remodeling of cardiolipin through dysregulation of mitochondrial acyltransferases could result in decreased cardiolipin generation, mitochondrial structural anomalies and impairment in cellular bioenergetics. One such example is Barth syndrome, in which a mutation causes decreased tafazzin function, leading to a multitude of clinical effects, coupled with impaired cellular bioenergetics due to reduced biologically active cardiolipin (Claypool et al, 2008(Claypool et al, , 2006(Claypool et al, , 2011Whited et al, 2013).…”
Section: Introductionmentioning
confidence: 99%